Presence of Pathare Prabhus in Kandivli Gaothan - Mumbai Archive Project Team (Jio Institute, 2024)
Ranjan Dattaram Tarabai Mhatre is a member of the Pathare Prabhu community. Alongside the Kolis, Bhandaris, and Agri communities, the Pathare Prabhus are among Mumbai’s early inhabitants. They migrated from the Saurashtra region in Gujarat to the Konkan coast in the 12th or 13th century CE, eventually settling in Mumbai.